(3TQM bWQ GdfOi hHd GdUOis - (3YHO Gddg Hf jhSa Hf CMeO GdCfUGQj GdeUQj GdfMhj , LeGd GdOjf , CHh eMeO, GHf gTGe J (B761 (3g` s
(3ChdgG (B:s
(3hHYO, agPg fcJ MQQJgG Ydi ebOeJj GdeSeGI HbWQ GdfOi hHd GdUOi, QGaYI dMLGHgG s
(3BNQgG (B:s
(3hefgG eG jcSQ dG ZjQ hgh GdHGbj hgPG BNQ eG CQOfG EedGAg Ydi gPg GdebOeI eTjO GdeYGfj, aMce GdCMcGe, eSJhaj GdCfhGY hGdCbSGe s
(3HChdgG Jedc eDQN SfI (B1242 (3g`s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B147 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B163 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B465s
Keywords: (3GdfMhs